The influence of the endotracheal tube cuff on the occurrence of ventilator-associated pneumonia - Kučan, Marko (Obzornik zdravstvene nege, 2015)
Introduction: An endotracheal tube enables patient ventilation, but also presents a risk of complications. The accumulation of subglottic secretions above the cuff may cause ventilatorassociated pneumonia. The purpose of the article is to establish the effect of the endotracheal tube cuff (shape and material, method of inflation, verifying and maintaining pressure) on the incidence of ventilator-associated pneumonia. Methods: A descriptive method with a systematic review of domestic and foreign literature was used. The literature was retrieved from electronic databases and the cooperative bibliographic/catalogue database. According to eligibility criteria, sixteen original scientific articles published in the last ten years were finally used. Data were processed with qualitative content analysis. Results: Cuff inflation control with a manometer and continuous measuring and adjustment of cuff pressure with modern equipment were found to be the safest methods. According to the articles on shape and material, conical polyurethane cuffs provide the best sealing. Discussion and conclusion: Ventilator-associated pneumonia is a serious complication in mechanically ventilated patients. Maintaining appropriate cuff pressure proved to be a very effective preventive measure. The research presented here is limited by the small number of available articles. Further research is needed before practical applications are attempted.
Keywords: cuff; material; mešiček; nursing; oblika; preprečevanje; pressure; prevention; shape; tlak; ventilator associated pneumonia; ventilatorska pljučnica; zdravstvena nega